"There are a lot of activities going on but how do you make those known" : the challenge of organizational environmental communication in ICT-company - Martikainen, Lari-Pekka (2012)
The purpose of this study is to identify the obstacles that are hindering organizational environmental communication among the target group in the case company. After identifying obstacles, this thesis tries to find solutions to improve organizational environmental communication and knowledge sharing among the target group. Case company in this study is ICT-sector company and the target group consists of engineers that are working mainly with datacenters. This study uses qualitative methods. The research material was obtained by theme interviews. Research data was analysed by sorting data in to different themes that rose up during the analysing phase. Four main obstacles were found for organizational environmental communication: lack of verbal support from the management of the company towards environmental issues, energy efficiency is the driving force in the case company not environmental efficiency, communication forums for environmental communication are lacking and finding of environmental information is difficult in the case company and lack of environmental communication in the case company. Improving methods and ideas were also searched for research material, previous studies and benchmarking of other ICT-sector companies. Develop proposals were created for the case company that based on improving four main obstacles that were found on based on the results of this study. Four main areas that need to be develop are: more and clearer environmental communication from the management, change of the main driver from energy efficiency to sustainable development, more environmental communication forums and easier access to the information, better use of environmental information in communication.